The views and experiences of smokers who quit smoking unassisted. A systematic review of the qualitative evidence. - Andrea L Smith; Stacy M Carter; Sally M Dunlop; Becky Freeman; Simon Chapman (PLoS ONE, 2015)
Background Unassisted cessation - quitting without pharmacological or professional support - is an enduring phenomenon. Unassisted cessation persists even in nations advanced in tobacco control where cessation assistance such as nicotine replacement therapy, the stop-smoking medications bupropion and varenicline, and behavioural assistance are readily available. We review the qualitative literature on the views and experiences of smokers who quit unassisted. Method We systematically searched for peer-reviewed qualitative studies reporting on smokers who quit unassisted. We identified 11 studies and used a technique based on Thomas and Harden's method of thematic synthesis to discern key themes relating to unassisted cessation, and to then group related themes into overarching concepts. Findings The three concepts identified as important to smokers who quit unassisted were: motivation, willpower and commitment. Motivation, although widely reported, had only one clear meaning, that is 'the reason for quitting'. Willpower was perceived to be a method of quitting, a strategy to counteract cravings or urges, or a personal quality or trait fundamental to quitting success. Commitment was equated to seriousness or resoluteness, was perceived as key to successful quitting, and was often used to distinguish earlier failed quit attempts from the final successful quit attempt. Commitment had different dimensions. It appeared that commitment could be tentative or provisional, and also cumulative, that is, commitment could be built upon as the quit attempt progressed. Conclusion A better understanding of what motivation, willpower and commitment mean from the smoker's perspective may provide new insights and direction for smoking cessation research and practice.